Despertando o interesse pela Botânica por meio de uma metodologia diferenciada e investigativa aplicada com alunos do Ensino Médio - Eliza dos Reis Silva (2020)
The present work seeks awakening and applying motivation in the process of learning Biology, mainly in the field of Botany, using motivation analysis and how it acts in the educational context when distinct methodologies are used. For such, we consider the contributions of cognitive social theory and the microtheories of self-efficacy and self-regulation, focusing on the student's experience and the construction of scientific knowledge. We will address the acquisition of knowledge as a change in the conceptual structures, using for this, differentiated teaching methodologies and strategies. To achieve this goal, a didactic sequence was elaborated in order to promote an understanding of botanical concepts in a pleasant way, with an investigative bias. The theme, in the area of Botany Angiosperms, was contextualized its main characteristic, which are the flowers and pollination, and was chosen because it is considered very contentist and conceptual, making the teaching and learning processes more difficult. A sequence was applied to 2nd year students of a public school, and besides being the final product of this Master's Conclusion Work (TCM), it allowed the discussion and analysis of the influence of motivation when using diffent methodologies and how they positively interfere in the construction of scientific knowledge.